2001
DOI: 10.1079/ssr200061
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of soil burial and smoke on germination patterns in seeds of selected Australian native plants

Abstract: Patterns of dormancy and smoke responsiveness in artificially buried seeds were investigated in eight native plant species from the species-rich mediterranean-type climate zone of south-western Australia. A comparison was made between germination and viability behaviour of shelf- and field-soil-stored seed, with and without smoke treatment, at least every 3 months. These comparisons corresponded with each of the four seasons. The species chosen germinated with the aid of smoke under field or glasshouse conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 22 publications
3
69
1
Order By: Relevance
“…A subsequent wave of germination from soil-stored seed-banks is a well-known phenomenon where seed germination is stimulated indirectly through responses to micro-environmental changes or directly through responses to high temperatures or chemical cues derived from smoke, charcoal or ash (Zackrisson et al 1996;Brown and van Staden 1997;Reyes and Casal 1998;van Staden et al 2000). The ecophysiological responses to such fire-related germination cues have been studied extensively on species in ecosystems with naturally occurring frequent fires such as the South African fynbos (van Staden et al 2000;Brown et al 2003), the Australian kwongan (Dixon et al 1995;Roche et al 1997;Tieu et al 2001;Read et al 2000; Thomas et al 2007), the North American chaparral (Keeley 1987; Keeley and Fotheringham 1988, 1998 and the Mediterranean maquis (Crosti et al 2006). A major active compound in the smoke response has recently been identified as karrikinolide (3-methyl-2H-furo[2,3-c]pyran-2-one), a derivate from the combustion of cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent wave of germination from soil-stored seed-banks is a well-known phenomenon where seed germination is stimulated indirectly through responses to micro-environmental changes or directly through responses to high temperatures or chemical cues derived from smoke, charcoal or ash (Zackrisson et al 1996;Brown and van Staden 1997;Reyes and Casal 1998;van Staden et al 2000). The ecophysiological responses to such fire-related germination cues have been studied extensively on species in ecosystems with naturally occurring frequent fires such as the South African fynbos (van Staden et al 2000;Brown et al 2003), the Australian kwongan (Dixon et al 1995;Roche et al 1997;Tieu et al 2001;Read et al 2000; Thomas et al 2007), the North American chaparral (Keeley 1987; Keeley and Fotheringham 1988, 1998 and the Mediterranean maquis (Crosti et al 2006). A major active compound in the smoke response has recently been identified as karrikinolide (3-methyl-2H-furo[2,3-c]pyran-2-one), a derivate from the combustion of cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that seeds of many Australian species are responsive to smoke and smoke products (Dixon et al, 1995;Flematti et al, 2004;Merritt et al, 2006), thermic pulsing (Tieu et al, 2001a), afterripening (Schutz et al, 2002) and light . Nevertheless, there remain a number of common Australian species that do not respond to these treatments and are difficult to germinate (Dixon et al, 1995;Tieu et al, 2001b;Merritt and Dixon, 2003). Acanthocarpus preissii, the subject of the present study, is a prime example of a species in this latter category.…”
Section: Introductionmentioning
confidence: 99%
“…It should, however, be noted that the type of smoke used is of tremendous importance; for instance, in the present study, aqueous smoke solution did not affect germination response of Andropogon gayanus while in Dayamba et al (2008), aerosol smoke delayed its germination. Seeds (even physically dormant) may also become responsive to smoke after some period of storage or soil burial (Roche et al, 1997a(Roche et al, , 1998Tieu et al, 2001a). There could also be discrepancies between laboratory results and field responses due to the fact that smoke may act as a deterrent against predation (Roche et al, 1997b), that is, untreated seed in control plots may be more palatable to predators than smoke-treated seeds.…”
Section: Discussionmentioning
confidence: 88%